Methods of determining the efficiency of the cotton regenator in the cleaning process - Mamajanov, Shavkatjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article describes the technology of cleaning cotton from large impurities and the working process of the regenerator machine, which separates cotton raw material from the wastes released from the devices. In addition, in the study, if the real value of the regenerator's cleaning and regeneration effects is low, it is recommended to check the technical condition of the regenerator and correct the detected defects, as well as to reduce the consumption of air from the pneumatic supply of the regenerator.